Genetic inactivation of Nupr1 acts as a dominant suppressor event in a two-hit model of pancreatic carcinogenesis. Issue 6 (11th September 2013) - Cano, Carla E; Hamidi, Tewfik; Garcia, Maria Noé; Grasso, Daniel; Loncle, Céline; Garcia, Stéphane; Calvo, Ezequiel; Lomberk, Gwen; Dusetti, Nelson; Bartholin, Laurent; Urrutia, Raul; Iovanna, Juan L
Abstract : Background: Nuclear protein 1 (Nupr1) is a major factor in the cell stress response required for Kras G12D -driven formation of pancreatic intraepithelial neoplastic lesions (PanINs). We evaluated the relevance of Nupr1 in the development of pancreatic cancer. Methods: We investigated the role of Nupr1 in pancreatic ductal adenocarcinoma (PDAC) progression beyond PanINs in Pdx1-cre;LSL-Kras G12D ;Ink4a/Arf fl/fl ( KIC ) mice. Results: Even in the context of the second tumorigenic hit of Ink4a/Arf deletion, Nupr1 deficiency led to suppression of malignant transformation involving caspase 3 activation in premalignant cells of KIC pancreas. Only half of Nupr1 -deficient; KIC mice achieved PDAC development, and incident cases survived longer than Nupr1 wt ;KIC mice. This was associated with the development of well-differentiated PDACs in Nupr1 -deficient; KIC mice, which displayed enrichment of genes characteristic of the recently identified human classical PDAC subtype. Nupr1 -deficient; KIC PDACs also shared with human classical PDACs the overexpression of the Kras-activation gene signature. In contrast, Nupr1 wt ;KIC mice developed invasive PDACs with enriched gene signature of human quasi-mesenchymal (QM) PDACs. Cells derived from Nupr1- deficient; KIC PDACs growth in an anchorage-independent manner in vitro had higher aldehyde dehydrogenase activity and overexpressed nanog, Oct-4 and Sox2 transcripts compared with Nupr1 wt ;KIC cells. Moreover, Nupr1 -deficient and Nurpr1 wt ;KIC cells differed in their sensitivity to the nucleoside analogues Ly101-4b and WJQ63. Together, these findings show the pivotal role of Nupr1 in both the initiation and late stages of PDAC in vivo, with a potential impact on PDAC cell stemness. Conclusions: According to Nupr1 status, KIC mice develop tumours that phenocopy human classical or QM-PDAC, respectively, and present differential drug sensitivity, thus becoming attractive models for preclinical drug trials.